Education Between Cultural “Canon” and the Future: “Classics” and Their Didactic Value - Witkowski, Lech (Journal of Vasyl Stefanyk Precarpathian National University, 2023)
The text considers various aspects of pedagogical reflections within the problematics, described and analysed as follows: (1) The future speeds up and surprises, also painfully, (2) Everyday experience as an enemy of the future, (3) How symbolic culture is functionning?, (4) On the possibility of appraisal of classics beyond the classicism, (5) On bureaucratic interference into a lively textual tissue, (6) Between conservative and liberal treating of traditions in culture, (7) Between social radicality and dialogic deconstruction of culture, (8) Illusions and traps of canonizations of cultural contents, (9) The conclusion: on cultural attitudes in didactics. The author discusses limits and paradoxes of imposing cultural canon within education perceived as initiation into culture. The latter is to be perceived as invisible environment constituting symbolic soil for the memory of signifiers which serve for self-expression, understanding of the Other and for creative autotranscendence and enrichment of the cultural patrimony for the next generations. The basic message of the text requests more profound educational perception and treatement of tradition in order to make it participate in influences becoming the energetic and symbolic background of cultural development at the same time critically revisited in order to meet the challenges of the future.